Reviews (New blackfriars, 1970)
Book reviews in this articles THE BODY AS LANGUAGE, Terry Eagleton. MARX BEFORE MARXISM, by David Mclellan THE PHILOSOPHY OF LUDWIG FEURBACH, by EugeneKamenka, Routledge & Kegan Paul FEUERBACH ET LA THEOLOGIE DE LA SECULARISATION, by Marcel Xhauffaire THE YOUNG HEGELIANS AND KARL MARX, by David McLellan DIALOGUE ET REVOLUTION, by. J. Girardi MARXISM IN THE TWENTIETH CENTURY by Roger Garaudy LOVING ON PRINCIPLE, by E. W. Dicken. Darton SACRA DOCTRINA, Reason and Revelation in Aquina, by Per Erik Persson POUR UNE POETIQUE DE LA FOI, ESSAI SUR LE MYSTERE SYMBOLIQUE, by J.-P, Manigne, O.P.